Pengaruh Pembelajaran Berbasis Video Youtube Terhadap Hasil Belajar Kognitif Siswa Dalam Mata Pelajaran IPAS Kelas IV Di SD 6 Bulungcangkring - Diana Primari Yonanda; Purbo Jati Kusumo; Riana Dewi Puspitasari; Nita Fitri Amaliyah; Nisa Wandiana Putri; Shofiyana Ramdani; Meliyasa Khorina Laili (ENGGANG: Jurnal Pendidikan, Bahasa, Sastra, Seni, dan Budaya, 2024)
This study aims to determine the effect of the application of instructional media or educational tools in the form of YouTube videos on cognitive learning outcomes of students in class IV Science Science at SD 6 Bulungcangkring. The method used in this study is a quantitative method with a two-sample paired T-test approach. Data collection techniques were carried out by providing instruments in the form of cognitive learning outcomes test questions using plant material with pretest and posttest techniques. The stages of data processing are carried out by presenting data using SPSS for windows and analyzing data in a descriptive form to be able to draw conclusions. The results of the study were: (1) the average pretest score was 72 and the posttest average score was 74.1; (2) there are significant values of 0.376 and 0.376 > 0.05, so it can be said that there is no difference but there is a difference in the average value so that it can be said that there is only a slight influence on student learning outcomes due to a lack of student focus.